Strategi Pengembangan Produk Wisata Sungai Landak Berbasis Konsep 4A: Meningkatkan Daya Tarik Wisata - Jannah, Adelia Miftahul (Politeknik Pariwisata Medan, 2024)
Tourist attraction is something that can encourage tourists to visit a tourist destination. Landak River Timbang Jaya Village, Langkat Regency is one of the cool and pleasant natural attractions. The purpose of this study was to identify the tourism potential of the Hedgehog River and to develop strategic steps in order to develop the Hedgehog River tourist attraction. Data collection was done through in-depth interviews, document studies and observations. Data analysis used descriptive qualitative analysis of tourism potential in Landak River and village government support in tourism development. The results showed that the tourism potential that can be developed in Landak River consists of natural tourism potential by providing adequate facilities to realize sustainable tourism development.